Evaluation of Choroidal Vascular Changes in Patients with Multiple Sclerosis Using Enhanced Depth Imaging Optical Coherence Tomography - Esen, Ebru; Sizmaz, Selcuk; Demir, Turgay; Demirkiran, Meltem; Unal, Ilker; Demircan, Nihal (Ophthalmologica (Basel), 2016)
Objective: To evaluate the choroidal thickness in patients with multiple sclerosis (MS) using enhanced depth imaging optical coherence tomography (EDI-OCT). Methods: In this observational comparative study, 68 eyes of 34 MS patients and 60 eyes of 30 healthy subjects were evaluated. All participants underwent complete ophthalmologic examination and OCT scanning. Choroidal thickness measurements were performed at seven points. Results: The mean subfoveal choroidal thickness was reduced significantly in MS patients (310.71 ± 61.85 μm) versus healthy controls (364.85 ± 41.81 μm) (p < 0.001). The difference was also significant at all six measurement points (p < 0.001 for all). Choroidal thickness measurements revealed no significant difference between MS eyes with a prior optic neuritis (ON) history (MS ON) and those without ON history (MS non-ON). Subfoveal choroidal thickness did not correlate with retinal nerve fiber layer and Expanded Disability Status Scale score, but reduced choroidal thickness was associated with longer disease duration (r = -0.28, p = 0.019) in MS patients. Conclusion: In MS patients, choroidal structural changes occur both in MS ON and MS non-ON eyes. The decreased choroidal thickness might provide evidence to support a potential role of vascular dysregulation in the pathophysiology of MS.